2018
DOI: 10.4236/ijcm.2018.93017
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictors of Depression among Adolescents in Ido Ekiti, South West Nigeria

Abstract: Background: Depression among adolescents has been recognized as a public health problem all over the world. In Nigeria, as in most developing countries, there is a need for more research on the epidemiology of adolescent depression as this will guide prevention, diagnosis and treatment. Objectives: The study sought to determine the one month prevalence and predictors of depression among a sample of in-school adolescents in a rural region in South West Nigeria. Materials and Methods: This was a cross sectional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
23
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 20 publications
5
23
5
Order By: Relevance
“…The prevalence of psychological stress was observed to be low among the in-school adolescents with only a few observed to have high prevalence of psychological stress. This was comparable to the study carried out by Oderinde et al (2018) and Omigbodun et al (2008) but very low compared to the study by Nagendra et al (2012) where the prevalence was determined to be 57.7%. This might be because of different instruments used and location in which the study was conducted.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The prevalence of psychological stress was observed to be low among the in-school adolescents with only a few observed to have high prevalence of psychological stress. This was comparable to the study carried out by Oderinde et al (2018) and Omigbodun et al (2008) but very low compared to the study by Nagendra et al (2012) where the prevalence was determined to be 57.7%. This might be because of different instruments used and location in which the study was conducted.…”
Section: Discussionsupporting
confidence: 85%
“…This might be because of the rate of industrialisation in Ibadan compared to Ido-Ekiti. The study showed that majority of the respondents stated that their parents were married and from a monogamous family and they have a close relationship with their parents and siblings which was similar to the study conducted in Ido-Ekiti (Oderinde et al, 2018). This implies that other factors might have contributed to the prevalence of psychological stress among the respondents since majority reported that they have a cordial relationship with their parents and siblings.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Depression is therefore a significant problem among Polish young girls and boys. Adolescent depression is a serious health care problem not only in Western countries, but also in developing countries, such as Kenya (prevalence is around 26.4%) and Nigeria (prevalence between 12.6 and 16.3%) (Oderinde et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Oderinde et al administered PHQ-9 modified for adolescents (PHQ-A) to 540 students in rural Nigeria as a screening tool for depression, followed by the depressive disorders module of Kiddies-Schedule for Affective disorders and Schizophrenia (K-SADS), and reported the weighted one-month prevalence of depression as 16.3% [ 22 ]. Alharbi et al, in a recent study in Saudi Arabia [ 23 ] among 1245 students, reported a whopping 74.0% prevalence of depression using PHQ-9 as the study tool.…”
Section: Discussionmentioning
confidence: 99%